2004
DOI: 10.1111/j.1744-7348.2004.tb00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of decreased‐rubisco phenotype between generations of wheat transformed with antisense and sense rbcS

Abstract: SummaryThe elite UK winter wheat cv. Riband was transformed with constructs containing rbcS in sense and antisense orientations driven by the maize ubiquitin promoter with a transformation efficiency of 1.2%. Of 77 primary transformants 31% of the sense‐rbcS transformed lines and 78% of the antisense‐rbcS transformed lines had decreased rubisco content compared to wild‐type and marker‐only controls, with decreases of up to 60%. However, in the T1 progeny which inherited the transgene, only 5% showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The reason for no increase in Rubisco protein in these plants is not known, but it is possible that the promoter used did not work efficiently. Mitchell et al (2004) described that the strength of the maize ubquitin promoter was not sufficient in wheat mesophyll tissues. Although the use of the CaMV 35S promoter has been successful in the antisense rbcS tobacco (Rodermel et al 1988, Hudson et al 1992, its characteristics are constitutive and not always efficient in green tissues in rice (Tada et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for no increase in Rubisco protein in these plants is not known, but it is possible that the promoter used did not work efficiently. Mitchell et al (2004) described that the strength of the maize ubquitin promoter was not sufficient in wheat mesophyll tissues. Although the use of the CaMV 35S promoter has been successful in the antisense rbcS tobacco (Rodermel et al 1988, Hudson et al 1992, its characteristics are constitutive and not always efficient in green tissues in rice (Tada et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Valjakka et al (2000) and Sillanpa¨a¨et al (2005) introduced a sense rbcS fused with the CaMV 35S promoter into silver birch. Mitchell et al (2004) also transformed wheat with a sense rbcS under the control of the maize ubiquitin promoter. Getzoff et al (1998) produced transgenic Arabidopsis with a construct of the sense rbcS from pea under the control of the CaMV 35S promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results, however, suggested that none of the transgenic lines accumulated more Rubisco than the wild type (Fig. 9B), and in transgenic wheat (Triticum aestivum), Ubi-RBCS expression failed to yield an increased Rubisco amount (Mitchell et al, 2004). On the other hand, we did not initially screen transformants for overexpression; rather, we sought lines with single insertions that correctly expressed the transgenes.…”
Section: Limitations To Rubisco Accumulation In Maizementioning
confidence: 99%
“…The nuclear transformation approach has been applied to evaluate the contribution of Rubisco in controlling photosynthesis and growth in annual and herbaceous plants, such as tobacco (Rodermel et al, 1988;Stitt et al, 1991;Masle et al, 1993;Sicher et al, 1994), wheat (Mitchell et al, 2004) and rice (Makino et al, 1997(Makino et al, , 2000Suzuki et al, 2007Suzuki et al, , 2009a. However, none of these efforts has resulted in the improved specificity of Rubisco to CO 2 .…”
Section: Introductionmentioning
confidence: 98%